The Role of Natural Killer T Cells in Cancer—A Phenotypical and Functional Approach - Krijgsman, Daniëlle; Hokland, Marianne; Kuppen, Peter J. K. (Frontiers in Immunology, 2018)
Natural killer T (NKT) cells are a subset of CD1d-restricted T cells at the interface between the innate and adaptive immune system. NKT cells can be subdivided into functional subsets that respond rapidly to a wide variety of glycolipids and stress-related proteins using T- or natural killer (NK) cell-like effector mechanisms. Because of their major modulating effects on immune responses via secretion of cytokines, NKT cells are also considered important players in tumor immunosurveillance. During early tumor development, T helper (TH)1-like NKT cell subsets have the potential to rapidly stimulate tumor-specific T cells and effector NK cells that can eliminate tumor cells. In case of tumor progression, NKT cells may become overstimulated and anergic leading to deletion of a part of the NKT cell population in patients via activation-induced cell death. In addition, the remaining NKT cells become hyporesponsive, or switch to immunosuppressive TH2-/T regulatory-like NKT cell subsets, thereby facilitating tumor progression and immune escape. In this review, we discuss this important role of NKT cells in tumor development and we conclude that there should be three important focuses of future research in cancer patients in relation with NKT cells: (1) expansion of the NKT cell population, (2) prevention and breaking of NKT cell anergy, and (3) skewing of NKT cells toward TH1-like subsets with antitumor activity.